2020
DOI: 10.1186/s12875-020-01324-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the process and outcome indicators of type 2 diabetes care: a cohort study from Eastern Finland, 2012–2017

Abstract: Background Evidence-based guidelines include concrete treatment targets that can be used as process and outcome indicators in the evaluation of the quality of healthcare services and diabetes care. Quality improvement can be evaluated by monitoring longitudinal trends in the care indicators on the system level. The aim of this study is to describe trends in the processes and outcomes of care among people with type 2 diabetes in North Karelia, Finland. Methods The data consist of all adults with type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…More care plan entries reflected longer follow-up periods and thus, longer diabetes durations, which worsened diabetic control [ 20 ]. Another study from Finland showed that the HbA1c levels fluctuated from year to year while the LDL levels decreased steadily [ 21 ]. An increasing number of consultations also implies the possibility that the doctor prescribed statins that improve LDL levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More care plan entries reflected longer follow-up periods and thus, longer diabetes durations, which worsened diabetic control [ 20 ]. Another study from Finland showed that the HbA1c levels fluctuated from year to year while the LDL levels decreased steadily [ 21 ]. An increasing number of consultations also implies the possibility that the doctor prescribed statins that improve LDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, T2D requires improvements in all its clinical outcomes. In the same study from Finland, the proportions of patients whose HbA1c and LDL were measured yearly were 75–78% and 67–69%, respectively, with relatively minor overall changes over time [ 21 ]. According to our results, monitoring was more scarcely performed in the usual care group than in either of the care plan groups, which may indicate that the actual clinical outcomes in the usual care group may be even worse.…”
Section: Discussionmentioning
confidence: 99%
“…These organizational changes might also have had some effect on the continuity of the care of patients and further the outcomes of care. 22 The major strength of this study is that the electronic health records cover all adults with type 2 diabetes living in the North Karelia and includes data from both primary and specialized care, and therefore selection bias, nonresponsiveness and missing laboratory data were avoided. The validity of diabetes diagnosis in the electronic health records is high as diagnosis is based on explicit, predefined criteria (ICD-10 code E11).…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of 2017, a major change in the organization of health services occurred when the Joint Municipal Authority for North Karelia Social and Health Services was established, joining the health service organizations of 14 municipalities. These organizational changes might also have had some effect on the continuity of the care of patients and further the outcomes of care 22 …”
Section: Discussionmentioning
confidence: 99%
“…In Finland, statin use has continuously increased among the general population and individuals aged over 65 years during 1995–2010 12 , 13 but after that remained stable in men and even decreased in women 2010–2015, leading to an increased sex gap in statin use 13 . A recent study on trends in T2D care in the North Karelia region, Finland, between 2012 and 2017 found increases in the LDL-C treatment target achievement (< 2.5 mmol/L) from 53.4 to 59.5% and in statin prescriptions from 65.7 to 71.0%, respectively 14 .…”
Section: Introductionmentioning
confidence: 99%